Primary school students´ and teachers´ opinions about interactive boards and their possible utilization in tuition - Klement, Milan (Revija za elementarno izobraževanje, 2012)
Nowadays, the utilization of information and communication technologies in all types of schools has become obvious. Information and communication technologies bring a significant number of positive effects which appropriately complete and support education. The generally declared necessity for integration of new media and new educational technologies into the educational process is a prerequisite for further development of pedagogical sciences and practice. Since, in this context, it is essential to promote new didactic techniques and methods derived from them, it is equally important to follow the development of target groups opinions and attitudes. As the authors of the presented study are not aware of an overall study dealing with this issue, we have decided, based on research execution, to find out primary school students and teachers opinions about the introduction of modern didactic tools such as interactive boards into teaching practice. The presented study introduces the progress, the process, and the results of this significant research.
Keywords: didactic tools; informacijsko-komunikacijska tehnologija; information and communications technology; ICT; IKT; Irkutsk International Airport; učni pripomočki; interactive boards; interaktivne table; digital presentation; digital technology; digitalne predstavitve; multimedia; osnovne šole